Molekulární epidemiologie invazivního meningokokového onemocnĕni v Ceské republice - Krízová, P; Kalmusová, J; Musílek, M (Epidemiologie, mikrobiologie, imunologie, 2006)
The study objective is to present results of clonal analysis of Neisseria meningitidis isolates from invasive meningococcal disease in the Czech Republic in 1993-2005. The method of multilocus sequence typing (MLST) revealed genetic heterogeneity of serogroup B isolates and homogeneity of serogroup C isolates. Three clonal sequence type complexes (STC-18, STC-32 and STC-41/44) prevailed among serogroup B isolates and almost a quarter of isolates have ST unclassifiable into clonal complexes. STC-11 showed clear predominance among serogroup C isolates. Hypervirulent clonal complex STC-11 prevailed in 1993-2004 while another clonal complex, STC-41/44, became more widespread for the first time in 2005. MLST analysis showed differences between the meningococcal population in the Czech Republic and those in western European countries and elsewhere. The results of clonal analysis of Neisseria meningitidis isolates from invasive meningococcal disease provide background information for evaluation of the adequacy of recommended measures in the focus of the disease and for updating the recommended vaccination strategy in the Czech Republic.
Keywords: sérotypizace; Neisseria meningitidis; Czech Republic; Meningococcal Infections; lidé; sekvenční analýza; Sequence Analysis; Humans; Serotyping; meningokokové infekce; Česká republika